Herpetología patagónica : XII. Los iguánidos del grupo Liolaemus fitzingeri en Chubut: datos serológicos y posición taxonómica - Scolaro, J. A. (1977)
Immunological tests and morphological observations are carried out on the polymorphic populations of Liolaemus fitzingeri melanops, from Peninsula Valdés and Puerto Madryn (Chubut). The identity of this form and the sympatric specimens referred to Liolaemus goetschi Müller and Hellmich is supported. The probable active speciation of the fitzingeri complex is pointed out, in accordance with the increasing serological distance between the still recognized subspecific taxa Liolaemus fitzingeri fitzingeri, Liolaemus fitzingeri canqueli and Liolaemus fitzingeri melanops.